(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Heavy metal exposure to lead is associated with severe neuronal impairment through oxidative stress mediated by reactive oxygen species. This study investigated the potential neuroprotective effect of esculin on the lead (Pb)-induced brain neurotoxicity C57bl/6 model. Four groups of mice were used for the study (control, lead acetate-treated (10 mg/kg), lead acetate and esculin (10 mg/kg +15 mg/kg) and esculin (15 mg/kg) alone treated for 14 consecutive days. Lead-induced alterations in the level of lipid peroxidation, nitric oxide, protein carbonyl, and enzymatic and non-enzymatic activity were measured in brain homogenates. Histological changes in the hippocampus and cortex were also examined. The results documented that PbAc significantly increased hippocampal and cortical lipid peroxidation and nitrite levels and decreased glutathione content, superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase activity. Histological observations of lead-induced neurotoxicity revealed severe damage and a reduction in neuronal density in the hippocampus and cortex. However, treatment with esculin rescued hippocampal and cortical neurons from PbAc-induced neurotoxicity by restoring the balance between oxidants and antioxidants and improvise motor coordination and memory activity. Esculin also attenuates the morphological damage and neuronal density in the hippocampal and cortex regions of C57bl/6 mice. Hence, the study suggests that esculin may be useful in combating lead acetate-induced neuronal injury.